Tool use by New World Halichoeres wrasses - Tariel-Adam, Juliette; Toledo, Jaqueline G.; O’Brien, C. E.; Floeter, Sergio R.; Brown, Culum (Coral reefs, 2025)
A diverse array of animals has evolved the ability to use tools (e.g., primates, parrots, octopus, crabs, and wasps), but the factors leading to tool use evolution are poorly understood. Fishes could provide insight into these factors via comparison of ecological and morphological differences between tool-using and non-tool-using species. Anvil use is one example of tool use by fish: the fish holds a hard-shelled prey item in its mouth and strikes it onto a hard surface (anvil) to open it. To date, anvil use has been described in 26 of the > 550 described wrasse/Labridae species. Through a community science program called Fish Tool Use , 16 new observations of anvil use were collected in five species of a monophyletic group of wrasses called the New World Halichoeres . These new observations provide the first evidence of anvil use by Halichoeres brasiliensis , H. poeyi and H. radiatus , and the first video evidence of anvil use by H. garnoti and H. bivittatus. They extend the geographic range of known anvil use by wrasses to a new region, the western Atlantic, making this behaviour even more widespread than previously reported. Video analysis revealed that wrasses are flexible in their anvil use: They did not have a preferred side of their body, they cracked open a diverse array of prey on a variety of anvil types, and often used many anvils and striking points for the same prey item. More observations are needed to determine the evolutionary origin of anvil use behaviour, its ecological drivers, costs, and benefits.